Efektivitas Sistem Digitalisasi dalam Akselerasi Pendapatan Asli Daerah - Nurul Qalbi Insaniah; Nurul Fuada; Indriana (Scimadly Publishing, 2026)
The digital transformation of public services is a strategic priority to enhance governmental efficiency and transparency. This study analyzes the implementation of the E-BPHTB system in Gowa Regency and its impact on Local Own-Source Revenue (PAD) using the Technology Acceptance Model (TAM) framework. The study used a descriptive qualitative approach, drawing on interview data, observations, and annual transaction reports from 2022 to 2024. The findings indicate that the E-BPHTB system significantly enhances operational efficiency by reducing document processing time from three days to one or two days. Furthermore, the system improves transparency and accountability, contributing to a 22.21% increase in transaction volume by 2023. Despite initial target fluctuations due to the implementation of the Land Value Zone (ZNT) regulation, the system has proven effective in minimizing tax leakage and sustaining revenue growth. It is concluded that the E-BPHTB system is a critical catalyst for fiscal independence, provided there is continuous commitment to infrastructure and human resource development